Children's Understanding of the Moral Values of Historical Fiction Story Books: "Ken Arok and Ken Dedes: Heroes Together" for Elementary School Students in Malang City - Hasmara, Nabila Syifa; Prianti, Desi Dwi (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The low moral literacy of elementary school children in Indonesia poses a serious challenge to the development of national character. Many students are more familiar with instant digital media than educational reading, thus the values of empathy, courage, and social responsibility are increasingly marginalized. This study aims to describe elementary school students in Malang City's understanding of the moral values contained in the historical fiction storybook Ken Arok and Ken Dedes: Pahlawan Bersama (Heroes Together). A qualitative approach was used, with projective interview techniques that allow children to express their moral understanding through visualization. Primary data were obtained from interviews with 11 students in grades 1–3, aged 6–9, while the analysis used Kohlberg's moral development theory framework at the pre-conventional level. The results showed that children recognized and understood moral values such as fair leadership, courage to stand up for the weak, friendship, and gender equality. Furthermore, they were also able to connect these moral messages to everyday experiences, so that the process of internalizing values was not only cognitive but also emotional. These findings confirm that illustrated historical fiction in children's literature can be an effective instrument for moral education and a means of preserving local culture. This research makes a theoretical contribution by expanding the study of children's moral literacy through a visual storytelling approach. It offers practical recommendations for teachers and children's book writers to use illustrated literature as a medium for character education.